Clinicopathological features and prognosis of Thai women with endometrioisis-associated ovarian carcinoma - Surprasert P. (2014)
This study was undertaken to evaluate the clinical features and survival outcomes of ovarian cancer patients who had associated pelvic endometrioisis. The medical records of 1076 patients with ovarian cancer treated at Chiang Mai University Hospital between 1995 and 2005 were reviewed. Among of these patients, 37 (3.4%) had associated pelvic endometriosis. The mean age of the patients was 44 years (25-62 years). The most common presenting sign and symptom was an abdominal mass (12), followed by abdominal pain (10), abdominal distension (7), abnormal uterine bleeding (2). Twenty-one (56.8%) patients were nulliparous and 14 (37.8%) were single. The stage distribution was stage I (24), stage II (4), stage III (4), and stage IV (1). Four patients had 2 primary carcinomas. The most common histology of the 37 patients was clear cell carcinoma (17) followed by endometrioid carcinoma (11). The estimated 5-year disease - free survival was 55.4%. In conclusion, most patients associated with endometriosis- associated ovarian carcinoma present with abdominal masses and pain. Clear cell CA is the most common histology in ovarian cancer patients who have associated endometriosis. Three fourths of the patients are in stage I and have favorable prognosis.